2013
DOI: 10.1242/jcs.132415
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic association of the ULK1 complex with omegasomes during autophagy induction

Abstract: SummaryInduction of autophagy requires the ULK1 protein kinase complex and the Vps34 lipid kinase complex. PtdIns3P synthesised by Vps34 accumulates in omegasomes, membrane extensions of the ER within which some autophagosomes form. The ULK1 complex is thought to target autophagosomes independently of PtdIns3P, and its functional relationship to omegasomes is unclear. Here we show that the ULK1 complex colocalises with omegasomes in a PtdIns3P-dependent way. Live-cell imaging of Atg13 (a ULK1 complex component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
264
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(286 citation statements)
references
References 49 publications
19
264
1
2
Order By: Relevance
“…Shortly after ULK1/Atg5 dot formation, Atg14L accumulates to form a dot overlapping the ULK1/Atg5 dot, possibly through an association of ULK1 and Atg14L mediated by the Exo84 exocyst complex [70]. Although the ULK1 complex is placed upstream of the PI3K complex [20,66], PI3K activity appears to stabilize ULK1/ Atg5 dot formation [69,71]. In addition, it was shown that most ULK1 dots are formed on pre-existing VMP1 dots [69].…”
Section: Autophagosome Formation On the Ermentioning
confidence: 99%
“…Shortly after ULK1/Atg5 dot formation, Atg14L accumulates to form a dot overlapping the ULK1/Atg5 dot, possibly through an association of ULK1 and Atg14L mediated by the Exo84 exocyst complex [70]. Although the ULK1 complex is placed upstream of the PI3K complex [20,66], PI3K activity appears to stabilize ULK1/ Atg5 dot formation [69,71]. In addition, it was shown that most ULK1 dots are formed on pre-existing VMP1 dots [69].…”
Section: Autophagosome Formation On the Ermentioning
confidence: 99%
“…The biogenesis of the phagophore is not fully understood, but it is generally believed to originate from specific omega‐shaped domains in the ER called omegasomes 13, 14, 15, found in close proximity to ER–mitochondria contact sites 16, 17. The phagophore expands by receiving membrane input through vesicle transport or membrane contact sites from different membrane sources, including ER‐exit sites (ERES) and the ER–Golgi intermediate compartment (ERGIC) 18, 19, 20, the Golgi apparatus 21, 22, mitochondria 23, 24 and the plasma membrane 21, 22, 25.…”
Section: Introductionmentioning
confidence: 99%
“…27 The Atg13 HORMA domain is required for localization of the Atg14-containing PtdIns3K complex, 27 and is thought to mediate this localization through associating with acidic lipids. 27,28 The remaining 3 components of the Atg1 complex (Atg17, Atg29, Atg31) constitutively form a stable ternary assembly that is localized to the PAS irrespective of the nutrient status in the cell. 29 During nonstarvation conditions, this assembly utilizes the Atg11 protein to promote its localization to the PAS.…”
Section: Introductionmentioning
confidence: 99%